2009
DOI: 10.1007/s10620-009-0970-6
|View full text |Cite
|
Sign up to set email alerts
|

A Functional SNP of the Interleukin-18 Gene Is Associated with the Presence of Hepatocellular Carcinoma in Hepatitis B Virus-Infected Patients

Abstract: Background/Aim The natural course of hepatitis B virus (HBV) infection is likely related to host immune factors. Interleukin-18 (IL-18) plays a significant role in immune defense. This study was undertaken to determine the association between the presence of hepatocellular carcinoma (HCC) and single-nucleotide polymorphisms (SNPs) in the IL-18 gene in HBV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
1
26
2
Order By: Relevance
“…A further two studies3839 were excluded because they included either patients with only liver cirrhosis or an aggregated patient population with HCC or liver cirrhosis. In the end, 8 studies1213141516171819 were included in the final meta-analysis based on our search strategy and inclusion criteria (Table 1). Of these 8 studies, all1213141516171819 evaluated the association between the -137 polymorphism and HCC risk (1,318 cases, 2,254 controls), while 7 studies12141516171819 evaluated the association between the -607 polymorphism and HCC risk (1,262 cases, 1,696 controls).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A further two studies3839 were excluded because they included either patients with only liver cirrhosis or an aggregated patient population with HCC or liver cirrhosis. In the end, 8 studies1213141516171819 were included in the final meta-analysis based on our search strategy and inclusion criteria (Table 1). Of these 8 studies, all1213141516171819 evaluated the association between the -137 polymorphism and HCC risk (1,318 cases, 2,254 controls), while 7 studies12141516171819 evaluated the association between the -607 polymorphism and HCC risk (1,262 cases, 1,696 controls).…”
Section: Resultsmentioning
confidence: 99%
“…Of these 8 studies, all1213141516171819 evaluated the association between the -137 polymorphism and HCC risk (1,318 cases, 2,254 controls), while 7 studies12141516171819 evaluated the association between the -607 polymorphism and HCC risk (1,262 cases, 1,696 controls). The distribution of genotypes in controls was consistent with Hardy-Weinberg equilibrium (HWE, P  > 0.05) in all but two studies1315. The overall quality of the included studies was adequate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, increased production of proinflammatory cytokines and chemokines, such as tumor necrosis factor-a (TNFa) (Park et al, 2010), interleukin-1b (IL-1b) (Okamoto et al, 2010), and interleukin-8 (IL-8) (Wei et al, 2007), interleukin-10 (IL-10) (Shin et al, 2003), interleukin-18 (IL-18) (Kim et al, 2009) have been reported to be associated with tumor and chronic inflammatory disease. These cytokines are produced by immune cells including various populations of lymphocytes, macrophages, and other cells.…”
Section: Introductionmentioning
confidence: 99%
“…The different outcomes of HBV infection are associated with genetic factors such as allelic variants in the human genome that may affect the progression of viral hepatitis after infection (Thursz, 2001). In addition, many reports have also suggested associations between genetic polymorphisms and the risk of HBV infection and/or HCC occurrence Park et al, 2010;Kim et al, 2003;Shin et al, 2003;Kim et al, 2006;Park et al, 2006;Park et al, 2007;Shin et al, 2007;Chun et al, 2009;Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%